'A very pleasant, safe, and effectual medicine': The serial comma in the history of English. Issue 2 (3rd April 2022) - Calle-Martín, Javier; Criado-Peña, Miriam
ABSTRACT: The present paper traces the historical development of the serial comma in the history of English until its eventual decline over the course of the twentieth century. The serial comma (also known as the Oxford comma or Harvard comma ) refers to the existence of a pause immediately before the conjunctions and / or (and sometimes nor ) in a series of three or more elements in a clause. Although the use of this mark of punctuation is no longer a desideratum in Present-day British English, it was a disseminated practice among seventeenth-, eighteenth- and nineteenth-century writers. In light of this, this work has been conceived with the following objectives: (a) to study the use and distribution of the serial comma in the period 1500–1999; (b) to evaluate its distribution in the two types of writing, i.e. handwriting and printing, and the level of variation across text types; and (c) to ascertain whether the number of elements in the series participates in its deployment. The source of evidence comes from The Málaga Corpus of Early English Scientific Prose (MCEESP), the corpus of Early English Medical Writing (CEEM) and A Representative Corpus of Historical English Registers (ARCHER 3.2).